If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + 6w = 9 Reorder the terms: 6w + -3y = 9 Solving 6w + -3y = 9 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '3y' to each side of the equation. 6w + -3y + 3y = 9 + 3y Combine like terms: -3y + 3y = 0 6w + 0 = 9 + 3y 6w = 9 + 3y Divide each side by '6'. w = 1.5 + 0.5y Simplifying w = 1.5 + 0.5y
| 5/3(6X-4)=7Y | | 2.3(2x+1)+2.2x= | | (-82)+8+(-31)-(-21)= | | Y/5+3=y/2 | | 24+-10b= | | 9n-2=3n+38 | | 260/70 | | (5/4)x=100 | | 69y=34(2y+3) | | x^2+5x-19=0 | | 11(c-8)=-2*11-4c | | 1/2(x-18)-5=0 | | 9-56+6= | | 24v^9w^7-30v^5w^2y^3=0 | | 4x-5=4+10 | | 9-9=3x+2x | | x^2+5k-19=0 | | 1/2(x-18)-5 | | -2(x-4)=18 | | -5=9+7x | | X=AW-AC^3 | | 18+(-59)+(-73)= | | 6y^2-3y=y-6 | | v-6=16 | | (1.50+2p).15=11.50 | | 7[2-(3+4x)]-2x=-9+2(1-15) | | -2(-5+4b)=-6b+8(b-5) | | -5+x=x+3 | | 2x+(35+35)=9.25 | | (3X-4)+(4X+2)= | | -9/b=5/6 | | 5(4*2-20)=4(5*2-25) |